The Financial Constraints and the Value of Cash Holdings: An Empirical Investigation of US Firms - Hao, Zhipeng (2016)
Abstract Financial constraint is an important problem when assessing the companies’ financial behaviours. This study investigates the cash flow sensitivity of cash, which is used for measuring the financial constraints; in addition, the impacts of cash holdings for both financially constrained and unconstrained firms are investigated; three proxies are used to classify the companies as constrained and unconstrained, which are dividend payout ratio, firm size and KZ index, respectively. By examining the US public firms during the period of 2005 to 2015, through utilizing the fixed effect model and GMM model, we conclude that the financially constrained firms hoard more cash reserves than the unconstrained firms; furthermore, the financially constrained firms have higher marginal value compared with the unconstrained firms, which means the firms face financial constraints will create more value with every extra dollar reserved.